2022
DOI: 10.1038/s41598-022-14539-6
|View full text |Cite
|
Sign up to set email alerts
|

RNA modification patterns based on major RNA modifications define tumor microenvironment characteristics in glioblastoma

Abstract: RNA modifications play a major role in tumorigenicity and progression, but the expression and function in glioblastoma (GBM) have not been well described. In this study, we developed a GBM score based on the differentially expressed genes (DEGs) between groups showing RNA modification patterns. We assessed the association between the GBM score and tumor microenvironment (TME) characteristics. Based on the gene expression of these regulators, we identified two clusters with distinct RNA modification patterns. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…mRNA modifications also appear to have functional roles in glioblastoma in controlling the expression of oncogenes and tumor suppressors [ 78 , 79 ]. Moreover, genomic studies revealed that the expression levels of selected RNA modification enzymes define the tumor microenvironment in glioblastoma [ 80 ]. We hypothesize that RNA modification enzymes retrieved in CSC-sEVs could promote preferential decoding of specific sets of genes to support stress response and survival.…”
Section: Discussionmentioning
confidence: 99%
“…mRNA modifications also appear to have functional roles in glioblastoma in controlling the expression of oncogenes and tumor suppressors [ 78 , 79 ]. Moreover, genomic studies revealed that the expression levels of selected RNA modification enzymes define the tumor microenvironment in glioblastoma [ 80 ]. We hypothesize that RNA modification enzymes retrieved in CSC-sEVs could promote preferential decoding of specific sets of genes to support stress response and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Previous database-based studies have suggested that the levels of six RNA modifications (m1A, m5C, m6A, m6Am, m7G and Ψ), including m6A, in pharmacogene RNA may influence drug treatment efficacy [31]. It has also been reported that expression profiles of RNA modification writers in glioblastoma, colorectal cancer and lung cancer can stratify cancer patients and predict treatment response to chemotherapy or immunotherapy with immune checkpoint inhibitors [17,18,32], but the actual RNA modification levels have not been validated. We found, for the first time, that RNA modifications can predict cancer grade and drug response.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Li and colleagues recognized this. It developed a GBM score’ based on the differentially expressed genes (DEGs) between groups showing RNA modification patterns of writers that catalyze m1A methylation, m6A methylation, APA, and A-to-I RNA editing [ 46 ]. Out of the 26 writers analyzed, 15 were found to be more highly expressed in tumor tissue than adjacent normal tissue.…”
Section: Rna Modification Patterns In Gliomamentioning
confidence: 99%
“…The immunosuppressive tumor microenvironment has been identified as the primary reason for the failure of immune therapy in GBM patients; currently, there are no FDA-approved immunotherapies for GBM [ 47 ]. Accumulating evidence has shown a strong correlation between RNA modifications, namely m6A, and immunomodulation, and thus the efficacy of immunotherapies in GBM patients [ 43 , 46 , 48 50 ]. This correlation does not appear to be unique to primary brain tumors, as similar data has been found in colorectal cancer [ 51 ], colon cancer [ 52 ], gastric cancer [ 42 ], bladder cancer [ 53 ], lung adenocarcinoma [ 54 ], and head and neck squamous cell carcinoma [ 55 ].…”
Section: Rna Modification Patterns In Gliomamentioning
confidence: 99%